Association between intestinal permeability and faecal microbiota composition in Italian children with beta cell autoimmunity at risk for type 1 diabetes. Issue 7 (30th March 2016) - Maffeis, Claudio; Martina, Alessia; Corradi, Massimiliano; Quarella, Sara; Nori, Nicole; Torriani, Sandra; Plebani, Mario; Contreas, Giovanna; Felis, Giovanna E.
Abstract: Background: Pancreatic organ‐specific autoimmunity in subjects at risk for type 1 diabetes (T1D) is associated with increased intestinal permeability and an aberrant gut microbiota, but these factors have not yet been simultaneously investigated in the same subjects. Thus, the aim of this study was to assess both intestinal permeability and gut microbiota composition in an Italian sample of children at risk for T1D. Methods: Ten Italian children with beta cell autoimmunity at risk for T1D and 10 healthy children were involved in a case–control study. The lactulose/mannitol test was used to assess intestinal permeability. Analysis of microbiota composition was performed using polymerase chain reaction followed by denaturing gradient gel electrophoresis, based on the 16S rRNA gene. Results: Intestinal permeability was significantly higher in children at risk for T1D than in healthy controls. Moreover, the gut microbiota of the former differed from that of the latter group: Three microorganisms were detected – Dialister invisus, Gemella sanguinis and Bifidobacterium longum – in association with the pre‐pathologic state. Conclusions: The results of this study validated the hypothesis that increased intestinal permeability together with differences in microbiota composition are contemporaneously associated with the pre‐pathological condition of T1D in a sample of Italian children. Further studies are necessary to confirm the microbial markers identified in this sample of children as well as to clarify the involvement of microbiota modifications in the mechanisms leading to increased permeability and the autoimmune mechanisms that promote diabetes onset. Copyright © 2016 John Wiley & Sons, Ltd.